Knowledge and awareness of diabetes mellitus as a risk factor of colorectal cancer among health and medical sciences students in Kuantan, Pahang - Abdul Ghani, Radiah (Universiti Sultan Zainal Abidin, 2022)
Studies have shown that there is a strong association between diabetes mellitus and colorectal cancer. The risk of colorectal cancer is reported to be increased by 19% for people with diabetes mellitus. However, the knowledge and awareness regarding diabetes mellitus as a risk factor for colorectal cancer in the local community in Pahang was yet to be determined. Therefore, to start with, this study aimed to evaluate the level of knowledge and awareness of diabetes mellitus as a risk factor for colorectal cancer among IIUM Kuantan students, the sociodemographic characteristics contributing to the levels and the correlation of the level of knowledge and awareness. A total of 127 IIUM Kuantan students participated in this crosssectional study by responding to a self-administered questionnaire that has been developed using the available literature on the association of diabetes mellitus and colorectal cancer. The questionnaire was first validated (I-CVI=1.00), and pilot study was also conducted to evaluate the reliability of the knowledge (α=0.788) and awareness (α=0.795) items using Cronbach’s alpha value. Then, data was collected throughout April 2022 by distributing the questionnaire through an online platform among the targeted participants. The results are analyzed with non-parametric tests: Mann-Whitney U and Kruskal Wallis test using the SPSS. Statistical significance was set at p<0.05 at a 95% confidence level. This study revealed a poor level of knowledge (n=82, 64.6%) and awareness (n=72, 56,7%) of diabetes mellitus as a risk factor of colorectal cancer among the IIUM Kuantan students. There was a moderate positive correlation between the level of knowledge and awareness of IIUM Kuantan students on diabetes mellitus as a risk factor of colorectal cancer (r=0.608, p<0.001). These levels of knowledge and awareness, however, were not significantly associated with any sociodemographic variables. Therefore, this study proves that there is a need to improve the knowledge and awareness of the IIUM Kuantan students. Hence, the university could take action by organizing programs to spread the knowledge on this issue to the students, in order to enhance their awareness of the risk of colorectal cancer by diabetes mellitus.